1998 Portuguese referendums: Explaining the results and speculating on the future of direct democracy in Portugal - Freire, A.; Baum, M. (Portuguese Journal of Social Science, 2003)
In 1998 Portugal held its first two national referendums since its democratic transition began in 1974. In theory, the referendums on liberalizing access to abortion and instituting a new regional level of governance represented a new opportunity for civil society groups to make their voices heard on important issues of the day, thereby revitalizing the quality of the country’s democracy. Instead, most Portuguese voters stayed at home and the status quo was maintained. Our paper, based on interviews with over forty national, regional and local-level political elites during 1998, offers a general overview of the institutional and political context of both referendums, of the campaigns and the results, and it seeks to explain the role of social structural factors, political parties, and pressure groups in both abstention and voting choices in the referendums. These findings are then used as a springboard for some tentative conclusions about the future of direct democracy in Portugal.